2020
DOI: 10.1177/1044389420947229
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Social Support on Caregiver Burden and Quality of Life for Compound and Noncompound Caregivers

Abstract: This study sought to explore the mediating effect of informal social support on the relationship between caregiver burden and quality of life among compound and noncompound caregivers. Parents ( N = 320) completed a web-based survey aimed to examine effects of caring for an adult child with autism spectrum disorder. Results of the mediation analysis suggested that informal social support partially mediated the relationship between caregiver burden and quality of life for both groups. Informal social support ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Caregiver participants who identified a source of social support were also found to be have less caregiver burden (ZBI‐12 of 16.3 ± 8.5 compared to 23.6 ± 9.4, p < .001). This finding is similar to recent literature that examined caregiver burden among both compound and noncompound caregivers of individuals with autism spectrum disorder (Marsack‐Topolewski, 2021). In that study, Marsack‐Topolewski (2021) found that both types of caregivers were found to have increased levels of burden when they reported less social support.…”
Section: Discussionsupporting
confidence: 90%
“…Caregiver participants who identified a source of social support were also found to be have less caregiver burden (ZBI‐12 of 16.3 ± 8.5 compared to 23.6 ± 9.4, p < .001). This finding is similar to recent literature that examined caregiver burden among both compound and noncompound caregivers of individuals with autism spectrum disorder (Marsack‐Topolewski, 2021). In that study, Marsack‐Topolewski (2021) found that both types of caregivers were found to have increased levels of burden when they reported less social support.…”
Section: Discussionsupporting
confidence: 90%
“…Also in the multiple regression model with the mental HRQoL as dependent variable, subjective caregiver burden explained most variance in family caregivers’ mental HRQoL. That is, the lower the perceived caregiver burden, the higher the mental HRQoL [in line with ( 26 , 41 )]. As described before, caregiver burden entails the demands, challenges, and stressors experienced by those who are providing care ( 41 ) on several dimensions, i.e., negative feelings resulting from informal caregiving, lack of support from family and friends, relationship problems, mental and physical health problems, problems with activities of daily living, and financial problems due to caregiving responsibilities ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the findings emphasize the importance of HRQoL as a relevant outcome not only in autistic adults but also in their family caregivers in order to obtain early indications of the family caregivers’ health status ( 70 ). Professionals working with autistic adults and their families should be aware that provided care may have an impact on the physical and mental health status ( 41 ). In addition, the findings highlight the need to address the lack of evidence on physical HRQoL in future research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mediation analysis also indicated that the participants’ perceived social support, whether from family, peers, or other significant individuals, mediated the relationship between courtesy stigma and life satisfaction among caregivers of youth with IDDs. The importance of social support as a protective factor for caregivers is well-documented, particularly in helping caregivers deal with stressors, such as stigma, which may eventually affect their mental health and well-being (Broady et al, 2017; Halstead et al, 2018; Lu et al, 2018; Marsack-Topolewski, 2021; McLean & Halstead, 2021). In the present study, caregivers who perceived a strong informal network and support from family, peers, and other significant individuals reported satisfaction with their lives despite the pervasive impact of courtesy stigma.…”
Section: Discussionmentioning
confidence: 99%